2021
DOI: 10.1002/ps.6402
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ABCG transporter genes associated with chlorantraniliprole resistance in Plutella xylostella (L.)

Abstract: BACKGROUND: Plutella xylostella (L.) is a serious worldwide pest that feeds on cruciferous plants and has evolved resistance to different classes of insecticides used for its control, including chlorantraniliprole. ATP-binding cassette (ABC) transporters, constituting the largest transport family in organisms, are involved in phase III of the detoxification process and may play important roles in insecticide resistance. RESULTS: A total of 15 ABC transporter transcripts from subfamily G were identified in P. x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 52 publications
2
28
0
Order By: Relevance
“…The field-resistant P. xylostella population BL was collected in vegetable fields in Boluo, Guangdong Province, in 2016 and then selected with chlorantraniliprole intermittently to maintain resistance. NIL is a near-isogenic resistant population that was obtained from SS and BL as previously [57]. The field-resistant population HK was collected from vegetable fields in Haikou, Hainan Province in 2016 and then constantly selected with chlorantraniliprole in our laboratory.…”
Section: Insectsmentioning
confidence: 99%
“…The field-resistant P. xylostella population BL was collected in vegetable fields in Boluo, Guangdong Province, in 2016 and then selected with chlorantraniliprole intermittently to maintain resistance. NIL is a near-isogenic resistant population that was obtained from SS and BL as previously [57]. The field-resistant population HK was collected from vegetable fields in Haikou, Hainan Province in 2016 and then constantly selected with chlorantraniliprole in our laboratory.…”
Section: Insectsmentioning
confidence: 99%
“…In addition, Guo et al [38] showed that ABCH1 was independent of Cry1Ac resistance, but the knock down of this gene could result in P. xylostella larval and pupal lethal phenotypes. Moreover, Shan et al [39] showed that ABCG was related to chlorantraniliprole resistance in P. xylostella. Nrgri et al [40] showed that silencing the ABCG4 gene resulted in an increased pyrethroid efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, knockdown of the ABCG15 gene significantly increased thiamethoxam sensitivity in the cotton aphid Aphis gossypii (Glover) (Hemiptera: Aphididae) ( Pan et al 2020 ), and knockdown of ABCG3 significantly reduced the survival rate of imidacloprid-treated Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) ( He et al 2019 ). In addition, silencing of ABCG6 , ABCG9 , and ABCG14 significantly increased the chlorantraniliprole susceptibility in Plutella xylostella (L.) (Lepidoptera: Plutellidae) ( Shan et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%